A MULTI-LEVEL SCALE OF TECHNICAL SAFETY INDICATORS OF URBAN LIFE SUPPORT SYSTEMS - Emelianov, Sergei Gennadievich; Gordon, Vladimir Alexandrovich; Bakaeva, Natalya Vladimirovna (Journal of Applied Engineering Science, 2017)
The article describes a multilevel scale of quantitative indicators of technical safety of an urban life support system. The described system is considered as a territorially – distributed structure with a complex of interacting subsystems. Indicatorsare presented in the form of multi-component vectors and describe conformity of the actual state of the system to regulatory requirements. As an example,indicators of technical safety of an urban water supply subsystem are calculated.